Pengaruh Ukuran Perusahaan dan Profitabilitas terhadap Kualitas Audit pada Perusahaan Sub Sektor Makanan dan Minuman di Bursa Efek Indonesia Periode 2022–2025 - Maya Al Zahra; Muwahhidin Muwahhidin; Ismail Ismail; Jamaluddin Jamaluddin; Muhammad Ansar (Journal of Applied Accounting, 2026)
This study aims to analyze the effects of firm size and profitability on audit quality among food and beverage subsector companies listed on the Indonesia Stock Exchange during the 2022–2025 period. Using a quantitative approach and the SEM-PLS method, the study employed 10 company samples selected through purposive sampling. The results indicate that firm size has a negative and significant effect on audit quality, whereas profitability has no significant effect. Keywords: Firm Size, Profitability, Audit Quality, Return on Assets (ROA), SEM-PLS.